2000
DOI: 10.1614/0890-037x(2000)014[0167:dohrat]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Defining Optimum Herbicide Rates and Timing for Wild Oat (Avena fatua) Control in Spring Wheat (Triticum aestivum)1

Abstract: Knowledge of optimal combinations of graminicide rate and stage of application could improve the effectiveness and net benefit of commonly used graminicides. A study was conducted at two locations in Saskatchewan, Canada, from 1994 to 1997. Factorial combinations of five graminicides (CGA 184927, fenoxaprop-p-ethyl, ICIA 0604, imazamethabenz, and flamprop-methyl), three graminicide rates (full, two-thirds, and one-third recommended label rate), and three leaf stages of wild oat (Avena fatua; two-, four-, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 7 publications
3
39
0
3
Order By: Relevance
“…espécies cultivadas, é observada com freqüên-cia na literatura (Olson & Nalejawa, 1981;Deschamps et al, 1990;Holshouser & Coble, 1990;Vidrine et al, 1995;Burke et al, 2004;Scherder et al, 2005). Nos Estados Unidos, Minton et al (1989) demonstraram que a associação de clodinafop-propargyl com herbicidas inibidores da ALS comprometeu o controle de Echinochloa crus-galli em taxas que variaram de 5 a 45%.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…espécies cultivadas, é observada com freqüên-cia na literatura (Olson & Nalejawa, 1981;Deschamps et al, 1990;Holshouser & Coble, 1990;Vidrine et al, 1995;Burke et al, 2004;Scherder et al, 2005). Nos Estados Unidos, Minton et al (1989) demonstraram que a associação de clodinafop-propargyl com herbicidas inibidores da ALS comprometeu o controle de Echinochloa crus-galli em taxas que variaram de 5 a 45%.…”
Section: Resultsunclassified
“…Já em dicotiledôneas essa tolerância se dá pela insensibilidade da ACCase (Vidal & Merotto Jr., 2001). A seletividade de trigo a clodinafop-propargyl pode ser ampliada com a mistura do protetor (safener ) clo quinto cet-me xyl, que pro teg e efi cientemente o trigo e parcialmente a cevada, mas não possui efeitos sobre a aveia e o azevém (Vencill, 2002 Deschamps et al, 1990;Holshouser & Coble, 1990;Vidrine et al, 1995;Brommer et al, 2000;Burke et al, 2002;Scherder et al, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[35,43] Several studies have demonstrated that this tactic can maintain effective weed control and sustain economically acceptable crop yields. [44,45] Conflicting results regarding success in using reduced herbicide rates may be due to a variety of factors such as spray volume, droplet size, adjuvants, temperature, humidity, light quality, soil moisture content, weed size and weed species. [44,46] Despite its potential effectiveness, legal factors present practical challenges to the implementation of reduced herbicide rates, as a person or organization recommending reduced rates may be held liable for problems arising from their use.…”
Section: Herbicide-based Tacticsmentioning
confidence: 99%
“…Efficacy of post-emergent herbicides is influenced by spray volume, droplet size, adjuvants, temperature, humidity, light quality, soil moisture content, weed size and weed species Holm et al 2000). More importantly, reduced rates are more likely to be consistently effective when weed densities are low, which will only occur with any regularity if the cropping system is managed to achieve this .…”
Section: Reduced Herbicide Ratesmentioning
confidence: 99%